Prevalence Assessment of the mecC Gene Among MRSA Clinical Isolates in a Malaysian Teaching Hospital - Wei Xuan Chang; Kon Ken Wong; Sharifah Azura Salleh; Hui-min Neoh; Muttaqillah Najihan Abdul Samat (Sains Malaysiana, 2026)
Methicillin-resistant Staphylococcus aureus (MRSA) resistance is predominantly mediated by the mecA gene; a novel homologue, mecC, has emerged among livestock-associated MRSA, and to date no data exist on the prevalence of human mecC-MRSA in Malaysia. This retrospective cross-sectional study aimed to determine the prevalence of mecC gene carriage and characterise the antimicrobial susceptibility profiles of 89 archived clinical MRSA isolates from 2023, using conventional PCR for gene detection and the VITEK 2 system for antimicrobial susceptibility testing. All isolates were mecA-positive, and none carried mecC. High resistance rates were observed against ciprofloxacin (89.9%, MIC90 ≥8 µg/mL), levofloxacin (88.8%, MIC90 ≥8 µg/mL), moxifloxacin (88.8%, MIC90 4 µg/mL), erythromycin (66.3%, MIC90 ≥8 µg/mL) and clindamycin (65.2%, MIC90 ≤0.25 µg/mL). All isolates remained susceptible to vancomycin (MIC90 1 µg/mL), linezolid (MIC90 2 µg/mL), quinupristin/dalfopristin (MIC90 ≤0.25 µg/mL), tigecycline (MIC90 0.25 µg/mL), nitrofurantoin (MIC90 32 µg/mL) and rifampicin (MIC90 ≤0.5 µg/mL). Susceptibility to trimethoprim/sulphamethoxazole and tetracycline was 95.5% (MIC90 ≤10 µg/mL and ≤1 µg/mL, respectively). One mecA-positive isolate was susceptible to oxacillin (MIC 0.5 µg/mL) and negative on cefoxitin screening, consistent with the oxacillin-susceptible MRSA (OS-MRSA) phenotype. This study confirms mecA as the sole methicillin-resistance determinant in this hospital; the absence of mecC likely reflects limited livestock exposure in this urban population, although surveillance in agricultural regions remains warranted. The detection of OS-MRSA highlights the limitations of relying solely on phenotypic screening and supports incorporating molecular assays to prevent misclassification.